DAMPAK BRAND COMMITMENT TERHADAP SERVICE STANDARD COMMUNICATION , ONLINE BRAND IMAGE DAN WORD OF MOUTH TERHADAP ONLINE BUYING INTENTION - Purwandari, Suci; Purnomo, Singgih (JURNAL ILMIAH EDUNOMIKA, 2023)
The purpose of this study was to determine the impact of brand commitment on service standard communication, online brand image and word of mouth on online buying intention in the digital era. The design of this study uses descriptive research and causality research, measuring each variable using a 5-point Likert scale. This study uses primary data by collecting data through questionnaires. The sampling used in this study was purposive sampling and a sample of 100 respondents was obtained. This study uses statistical methods with SMART PLS as a testing tool. The results of this study indicate that brand commitment has no influence on online buying intention. Whereas online brand image has an influence on service standard communication and word of mouth, then online brand image and word of mouth have a positive influence on online buying intention among digital era users. Keywords: Brand Commitment, Service Standard Communication, Online Brand Image, Word of Mouth, and Online Buying Intention